Teologiczne podstawy wizji historii w poezji Krzysztofa Kamila Baczyńskiego - Baran, Justyna (Śląskie Studia Polonistyczne, 2011)
The image of God in ***[„Śnieg jak wieko żelazne”…] by Krzysztof Kamil Baczyński may become not only a key to the poem interpretation, but also a starting point for considerations concerning the poet’s perception of history. Theological aspects are tightly connected with historio-philosophical ones whereas the image of God reflects the changes taking place in the subject of the poem as it recognizes the sense of the history. A diagnosis concerning the history of the world, formulated in the poem, is the result of the image of God in which Christian, Judaic and mythological elements have been combined. The very measures give an insight into an effort taken in order to search for the sense of the history at the time of extermination. At the same time, however, one can notice „self-therapeutic” actions , the subject of the text finds the world’s Logos. Also, poet’s poetical imagination, contaminated with cruelty and evil, gets restored.